Verbal and Non-verbal Signs of Starbucks Advertisements - Casmita, Putu; Pratiwi, Desak Putu Eka; Tustiawati, Ida Ayu Mela (Austronesian: Journal of Language Science & Literature, 2024)
Advertisements are an effort of the company to attract the customer’s attention by using attractive colours, words, pictures, and so on. Hopefully, the product that they sell will be better known by the people. This study presents the verbal and non-verbal signs contained in the Starbucks advertisement. Besides presenting verbal and non-verbal signs, this study also explains the meaning of the verbal and non-verbal signs. Two Starbucks advertisements were used as data sources. The data source has been taken from the internet. The theory used in this study is the theory of semiotics that was proposed by Saussure (1983) to describe verbal and non-verbal signs. The theory proposed by Barthes (1977) to analyse the meaning of verbal and non-verbal signs and the supporting theory of the meaning of colours was proposed by Wierzbicka (1996). As a result, the writer found six (6) verbal signs and six (6) non-verbal signs in this Starbucks advertisement.